色, 戒 = Lust, caution [videorecording (DVD)] - Desplat, Alexandre (Focus Features spotlight series., 2008)
Set in Japanese-occupied Shanghai, a young woman finds herself swept up in a radical plot to assassinate a ruthless and secretive intelligence agent. As she immerses herself in her role as a cosmopolitan seductress, she becomes entangled in a dangerous game of emotional intrigue, love and betrayal.